2000
DOI: 10.1111/j.1095-8339.2000.tb01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of a mycoheterotrophic species, Burmannia wallichii (Burmanniaceae)

Abstract: Received Jub 1999; acceptcdfor publtkation ~t c m b e r I999The breeding system of a mycoheterotrophic species, Bumannia wullkhii (Miers) Hook. f.(Burmanniaceae), is assessed using field observations, floral anatomy, pollen histochemistry and isozyme electrophoresis. The structure of the flower effectively prevents pollinators from accessing the stamens, and no pollinators were observed visiting natural populations in Hong Kong. The pollen is starch-rich but lipid-poor. Analysis of isozyme variation revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In his experiments, Geitler (1956) noted a similar percentage of seed capsules on flowering shoots that were manually self-pollinated or cross-pollinated. Some studies have suggested that autonomous self-pollination may be favourable for mycoheterotrophic plants, as they have limited access to carbon sources (Takahashi et al, 1993;Zhang and Saunders, 2000;Lehnebach et al, 2005) and are restricted to shaded forest understorey habitats with a paucity of pollinators (Dressler, 1993;Leake, 1994). However, the variety in flower morphology of many mycoheterotrophic plants instead suggests the diversity of breeding systems and pollinators, as has been confirmed by studies into the reproductive biology of Voyria (Hentrich et al, 2010) and Monotropoideae (Klooster and Culley, 2009).…”
Section: Flowers Of Epipogium Aphyllum Are Capable Of Autogamymentioning
confidence: 97%
“…In his experiments, Geitler (1956) noted a similar percentage of seed capsules on flowering shoots that were manually self-pollinated or cross-pollinated. Some studies have suggested that autonomous self-pollination may be favourable for mycoheterotrophic plants, as they have limited access to carbon sources (Takahashi et al, 1993;Zhang and Saunders, 2000;Lehnebach et al, 2005) and are restricted to shaded forest understorey habitats with a paucity of pollinators (Dressler, 1993;Leake, 1994). However, the variety in flower morphology of many mycoheterotrophic plants instead suggests the diversity of breeding systems and pollinators, as has been confirmed by studies into the reproductive biology of Voyria (Hentrich et al, 2010) and Monotropoideae (Klooster and Culley, 2009).…”
Section: Flowers Of Epipogium Aphyllum Are Capable Of Autogamymentioning
confidence: 97%
“…The entire genus Burmannia is likely to possess a prominent entomophilous floral syndrome, as defined by Faegri and van der Pijl (1979) . This idea has already been proposed for various species of the genus ( Spitmann, 1975 ; Maas et al., 1986 ; Zhang and Saunders, 2000 ). Flowers of Burmannia are brightly coloured; in B. disticha , yellow tepal lobes contrast with the violet floral tube and ovary.…”
Section: Discussionmentioning
confidence: 91%
“…At the same time, the majority of species likely benefit from pollen-derived nutrients when consuming pollen-contaminated nectar ( Baker and Baker, 1975 ; Romeis et al., 2005 ). Pollen of Burmannia (including B. disticha ) was indicated as starch-rich but lipid-poor ( Zhang, 1999 ; Zhang and Saunders, 2000 ), which is typical of plants pollinated by Lepidoptera ( Baker and Baker, 1983 ). Although Zhang and Saunders (2000) stated that “the small size of Burmannia flowers and the inaccessible anthers preclude wind-pollination or pollination by Lepidoptera or birds”, our data allow to refute this idea at least regarding Lepidoptera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ernst and Bernard, 1912) and B. wallichii (Miers) Hook.f. (Zhang and Saunders, 2000). Burmannia coelestis is reported to be apomictic (Ernst, 1909).…”
Section: Reproductionmentioning
confidence: 99%